Geomorphological study of Quaternary tectonics of the Doon Valley, Garhwal Himalaya, Uttranchal, India - Patel, R. C.; Kumar, Yogesh (Journal of Nepal Geological Society, 2003)
The post-major Himalayan tectonics is distinctly reflected on the present day topography of the Doon Valley. The photogeological characters and field study show that the Doon Valley is bounded by major faults. NE-dipping Main Boundary Thrust (MBT) surrounds it in the north, Mohand Thrust and Bhimgoda Thrust in the south, the Ganga Tear Fault in the east and the Yamuna Tear Fault in the west. Due to ongoing continental convergence of the Indian and Eurasian plates, the valley is tectonically unstable today. Vertical as well as horizontal movements are ongoing processes of the valley. The terraces along river valleys, bending of the river courses, tilting of the piedmonts, shifting of the river courses, overriding of the Lesser Himalayan rocks over the Doon Valley and Siwalik rocks over Indo-Gangetic plain are the consequence of it. Several lineaments, majorly longitudinal and transverse, are tearing up the Doon Valley. Out of them, some have segmented the recent Doon gravels, which reflect the Quaternary tectonics of the Doon valley. The probable cause of the Quaternary tectonics of the Doon Valley might be due to the northward pushing of the Delhi-Haridwar ridge.